The Prophetic Mission of Prophet Ibrahim a.s.: Strategies, Implementation Models, and Challenges in Prophetic Life - Ahmad Zainal Mustofa (Matan : Journal of Islam and Muslim Society, 2026)
Abstract: This study aims to analyze the concept of Islamic dawah and the dawah strategies implemented by Prophet Ibrahim in facing the challenges of preaching to his community, which was predominantly immersed in idol worship. The approach used by Prophet Ibrahim in his dawah is highly relevant as an example of effective dawah practice even today. Based on the analysis, the dawah of Prophet Ibrahim was not only verbal but also emphasized personal exemplary behavior, patience, and wisdom in dealing with rejection and challenges from his community. Through a rational and compassionate approach, Prophet Ibrahim was able to deliver the message of monotheism in a way that respected freedom of opinion without imposing his will. This study found that the dawah strategies of Prophet Ibrahim can be adapted to contemporary dawah contexts, where the importance of adapting to the social and cultural conditions of society is a key factor in the success of dawah. The success of Prophet Ibrahim’s dawah shows that a dawah based on exemplary behavior, patience, and compassion can build awareness and social change in a society trapped in misguidance. This research illustrates that effective dawah requires a wise approach, and relevance to the target audience’s conditions, and should not be limited to theory but also to concrete actions. Keyword: dawah strategies; implementation; challenges; Prophet Ibrahim; monotheis Abstrak: Penelitian ini bertujuan untuk menganalisis konsep dakwah Islam serta strategi dakwah yang diterapkan oleh Nabi Ibrahim a.s. dalam menghadapi tantangan dakwah kepada masyarakatnya yang mayoritas terjerumus dalam penyembahan berhala. Pendekatan yang digunakan oleh Nabi Ibrahim a.s. dalam dakwahnya sangat relevan sebagai contoh praktik dakwah yang efektif hingga saat ini. Berdasarkan analisis, dakwah Nabi Ibrahim a.s. tidak hanya bersifat lisan, tetapi juga mengutamakan keteladanan pribadi, kesabaran, dan kebijaksanaan dalam menghadapi penolakan serta tantangan dari masyarakatnya. Dengan pendekatan yang rasional dan penuh kasih, Nabi Ibrahim a.s. berhasil menyampaikan pesan tauhid dengan cara yang menghargai kebebasan berpendapat, tanpa memaksakan kehendak. Melalui penelitian ini, ditemukan bahwa strategi dakwah Nabi Ibrahim a.s. dapat diadaptasi dalam konteks dakwah masa kini, di mana pentingnya penyesuaian dengan kondisi sosial dan budaya masyarakat menjadi faktor kunci dalam keberhasilan dakwah. Keberhasilan dakwah Nabi Ibrahim a.s. menunjukkan bahwa dakwah yang berbasis pada keteladanan, sabar, dan penuh kasih dapat membangun kesadaran dan perubahan sosial dalam masyarakat yang terbelenggu oleh kesesatan. Penelitian ini memberikan gambaran bahwa dakwah yang efektif membutuhkan pendekatan yang bijaksana dan relevansi terhadap kondisi sasaran dakwah, serta tidak terbatas pada teori tetapi juga tindakan nyata. Kata kunci: strategi dakwah; penerapan; tantangan; Nabi Ibrahim a.s.; tauhid